2012
DOI: 10.1093/jnci/djr541
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life, Fertility Concerns, and Behavioral Health Outcomes in Younger Breast Cancer Survivors: A Systematic Review

Abstract: Younger women with breast cancer were found to experience distinct psychosocial and menopause-related concerns, weight gain, and physical inactivity. A need for more longitudinal research, including efforts at intervention to manage these symptoms and adverse health outcomes, remains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
510
4
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 711 publications
(564 citation statements)
references
References 92 publications
30
510
4
6
Order By: Relevance
“…Also, this method reached 37 years using another method of cut point of cancer survival time which is inconsistent with the result of this paper (Contal and O'Quigley, 1999). Various cut points were used in different breast cancer studies; for instance, GayosoDiz et al in Spain (2013), Anderson et al (2012), DeSanctis et al in the US (2011) used 50 cut point for age which are consistent with the results of this study. However, Alieldin et al (2014) used 40 cut point for age.…”
Section: Discussioncontrasting
confidence: 62%
“…Also, this method reached 37 years using another method of cut point of cancer survival time which is inconsistent with the result of this paper (Contal and O'Quigley, 1999). Various cut points were used in different breast cancer studies; for instance, GayosoDiz et al in Spain (2013), Anderson et al (2012), DeSanctis et al in the US (2011) used 50 cut point for age which are consistent with the results of this study. However, Alieldin et al (2014) used 40 cut point for age.…”
Section: Discussioncontrasting
confidence: 62%
“…Although we did not see major differences in QoL based on age, possibly due to small sample size, other studies have suggested that standardized measures of QoL identify worse outcomes and more frequent depressive symptoms in breast cancer survivors aged 50 years or younger when compared with the general age-matched population of women without cancer and to older women (aged >50 years) with breast cancer [24].…”
Section: Resultscontrasting
confidence: 89%
“…This has substantially changed to encompass the period immediately after the completion of treatment, including those who were symptoms-free or had recurrence until his or her death (Odle, 2011). This is also the period whereby survivors may be at risk of developing long-term physical and psychological complications of the disease and/ or its array of treatment including mastectomy, radiotherapy and chemotherapy (Howard-Anderson et al, 2012). While data on the survivors' long-term physical health and their quality of life have considerably accumulated, greater attention to examine the psychological states of the survivors are needed to provide emotional support and care during survivorship.…”
Section: Introductionmentioning
confidence: 99%